KETERKAITAN PELATIHAN KERJA DAN SELF EFFICACY DENGAN PENINGKATAN KINERJA KARYAWAN PT. POS INDONESIA (PERSERO) CABANG SUMBAWA BESAR - Fitriyani, Ika; Sudiyarti, Nining; Anjelita, Dela (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to examine the relationship between job training and self-efficacy with improving employees’ performance of PT. Pos Indonesia (Persero) Sumbawa Besar Branch. The type of this study used was associative study. The type of this study was associative study which aims to determine the effect of job training and self-efficacy on employees’ performance of PT. Pos Indonesia (Persero) Sumbawa Besar Branch. The type of data used in this study was quantitative data obtained directly from research respondents using a questionnaire. The respondents for this study were all employees of PT. Pos Indonesia (Persero) Sumbawa Besar Branch, totaling 40 people. The data used in this study were processed with SPSS software for analysis using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient testing (R2). The results of this research show that job training and self-efficacy have a positive and significant effect on employees’ performance of PT. Pos Indonesia (Persero) Sumbawa Besar Branch, both partially and simultaneously. The contribution of job training and self-efficacy in influencing employees’ performance of PT. Pos Indonesia (Persero) Sumbawa Besar Branch was 66.8%, while the remaining of 33.4% was influenced by other variables not examined in this study, such as leadership style, work motivation and compensation.